2014
DOI: 10.5624/isd.2014.44.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Development of dental charts according to tooth development and eruption for Turkish children and young adults

Abstract: PurposeIn this study, we aimed to develop dental charts for Turkish children and young adults of both genders within the age group of 4.5-22.5 years according to tooth mineralization and eruption in a format similar to that proposed by AlQahtani et al.Materials and MethodsIn total, 753 digital panoramic radiographs from 350 males and 403 females were assessed. The permanent teeth were evaluated according to the classification system described by Demirjian et al. The eruption stage was assessed with Bengston's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 33 publications
2
16
1
5
Order By: Relevance
“…However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults. In previous studies conducted in Turkish populations, it has been reported that dentition shows gender differentiation, with that in females preceding that in males [13][14][15]17,19,21]. Karadayi et al [19] described that this difference was usually in only one stage and not in all teeth.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults. In previous studies conducted in Turkish populations, it has been reported that dentition shows gender differentiation, with that in females preceding that in males [13][14][15]17,19,21]. Karadayi et al [19] described that this difference was usually in only one stage and not in all teeth.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies conducted in Turkish populations, it has been reported that dentition shows gender differentiation, with that in females preceding that in males [13][14][15]17,19,21]. Karadayi et al [19] described that this difference was usually in only one stage and not in all teeth. In this study, similarly with Karadayi et al [19] females show faster dental maturation than males in one stage (17.0-17.9) (P=006) ( Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Son yıllarda ise AlQahtani ve arkadaşları (13) tarafından Londra atlası ve Blenkin ve Taylor (14) tarafından Avustralyalı çocuklara spesifik birer atlas daha yayınlanmıştır. Bu alanda en son yayınlanan atlas K a r a d a y ı v e a r k a d a ş l a r ı t a r a f ı n d a n T ü r k i y e popülasyonuna özgü oluşturulan atlastır (15). Bu atlas 5-22 yaş aralığında ve her iki cinsiyet için yaşlara göre diş gelişimini gösteren çizimleri içermektedir.…”
Section: Gi̇ri̇ş Ve Amaçunclassified